The Impact of Fetal Echocardiography on Altering Course of Action Following A Prenatal Diagnosis of Congenital Heart Disease-A Thought Analysis - Khalil, Adiba Akhtar; Ara, Andaleeb; Akhtar, Khurram; Khan, Sumaira; Yaqub, Umairah; Akhtar, Joodi kizilwarda (Pakistan Armed Forces Medical Journal, 2023)
Objective: To assess the impact of fetal echocardiography in altering the course of action for neonatal cardiac expertise and services available in Pakistan following an antenatal diagnosis of congenital heart defect (CHD).Study Design: Cross-sectional study.Place and Duration of Study: Pediatric Cardiology Unit, Armed Forces Institute of Cardiology & National Institute of Heart Diseases, Rawalpindi Pakistan, from Feb 2020 to Sep 2021.Methodology: Fetuses aged 18 to 38 weeks of gestational age referred to the Pediatric Cardiac Unit due to risk of or suspicion of congenital heart disease underwent fetal cardiac echo. Data were collected and reviewed retrospectively to seek any impact of the antenatal diagnosis on post-natal planning.Results: The mean age of the mothers was 29.79±5.24 years (range, 17-47 years), and the mean gestational age at which the fetal echocardiography examination was performed was 27.29±4.47weeks (range: 12–38 years). Of the 609 pregnancies, fetal echocardiogram evaluation was performed, and sixty-three (10.3%) fetal echocardiograms were abnormal. Of the 63, only 06(9.5%) returned to the neonatal cardiac unit for follow-up and treatment in the first ten days of life.Conclusion: The real impact of fetal echocardiography is possible only with the availability of well-developed, readily accessible fetal and neonatal cardiac services. Poverty and a struggling healthcare infrastructure confound the benefits.